Rancang Bangun Website Smk Al-Ishlah Pulokulon Menggunakan Content Management System Wordpress - SETIABUDI, DIMAS ADI, Dr. Heru Supriyono, M.Sc (2016)
The increasing importance of information and is supported by a computerized system that can transform into a modern manual and can improve performance on a company, especially educational institutions. In educational institutions, the most important information is the time of sale of the school. Because the activity aims to provide information to prospective students, students, and community. So the development of this website focuses on company profile school used as a promotional medium school. In the analysis and website development SMK Al-Ishlah Pulokulon method waterfall method .. The aim of this study This study aims to develop a school website at SMK Al -Ishlah Pulokulon as an alternative to the provision of information and communication, and how effective the development of the school wesbite. Stages of development in this study begins by analyzing requirements, designing, creating school websites using WordpressContent ManagementSystem, After that applied then tested the effectiveness. Based on this research can be concluded that the school website using Wordpress CMS is included in both categories. In terms of its application website SMK Al-Ishlah Pulokulon suitable and effective as an alternative to the provision of information. The process of giving information on SMK Al-Islah Pulokulon more effective after the presence of the website. Keyword : Website, SMK Al-Ishlah Pulokulon, Wordpress